THE RELATIONSHIP BETWEEN WORKLOAD, TECHNOSTRESS, WORK LIFE BALANCE AND EMPLOYEE PERFORMANCE IN THE REGIONAL SECRETARIAT OF THE CITY OF SURABAYA: HUBUNGAN ANTARA WORKLOAD, TECHNOSTRESS, WORK LIFE BALANCE DAN KINERJA PEGAWAI DI SEKRETARIAT DAERAH KOTA SURABAYA - Reny Elvira Septyandini; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Bureaucratic Reform is one way to achieve good governance and make fundamental changes and renewals to the government administration system, especially in terms of institutional (organizational), administrative and human resource aspects. Through improvements to human resources. This study was conducted at the Regional Secretariat of Surabaya City with the aim of determining the relationship between the influence of workload, technostress, work life balance and employee performance. The research method is a quantitative approach where variables are measured using a Likert scale. The population in this study were employees who use technology in their work. Sampling was taken with a 95% confidence level using the Slovin technique, 193 people were obtained. The research variables consist of three independent variables, namely workload, technostress, work life balance and the dependent variable is employee performance. Data collection was carried out by distributing questionnaires. The results of the data collection were then analyzed using the Structural Equation Modeling Technique using the SMART PLS – 3 application. The results of the study showed that: (1) Workload has a positive effect on Technostress at the Surabaya City Regional Secretariat (2) Technostress does not affect Employee Performance at the Surabaya City Regional Secretariat. (3) Workload does not affect Employee Work Life Balance at the Surabaya City Regional Secretariat. (4) Work Life Balance has a positive effect on Employee Performance at the Surabaya City Regional Secretariat (5) Technostress has a negative effect on Work Life Balance at the Surabaya City Regional Secretariat (6) Workload does not have a significant negative effect on Employee Performance at the Surabaya City Regional Secretariat.